Photosynthetic nitrogen- and water-use efficiencies in C3 and C4 subtype grasses grown under two nitrogen supply levels - Yuko Togawa (Taylor & Francis Group, 2021)
C4 plants have higher photosynthetic nitrogen- and water-use efficiencies (PNUE and PWUE) than C3 plants. Some studies on C4 grasses have reported that NADP-malic enzyme (NADP-ME) grasses have higher PNUE than NAD-malic enzyme (NAD-ME) grasses, whereas other studies have suggested that this difference is caused by the traits of phylogenetic lineage. Further extensive studies are required to understand properly the PNUE and PWUE of C4 grasses. We investigated the PNUE and PWUE for 22 grass species of four photosynthetic types [4 NADP-ME, 6 NAD-ME, 6 phosphoenolpyruvate carboxykinase (PCK), and 6 C3 species] grown under two N supply levels. Under the same N level, the three C4 types showed higher photosynthetic rate and lower stomatal conductance and transpiration rate than the C3 type, but these parameters were similar in the C4 types. Although there were no significant differences in leaf mass per area and N content per leaf area among the four types, these traits tended to be somewhat lower in the NADP-ME type than in other types. As a result, PNUE was highest in the NADP-ME type, lowest in the C3 type, and intermediate in the NAD-ME and PCK types. PWUE was much higher in the C4 types than in the C3 type but similar in the C4 types. The N supply level did not greatly affect the trends of PNUE and PWUE. This study suggests that the NAD-ME and PCK grasses have the N-related physiological traits similar to each other but differing from the NADP-ME grasses.